The impact of family type on resilience levels of adolecentes from Lima and Huanta - Cantoral Gonzales, Camila Estefany (2020)
The purpose of the following research is to analyze and compare the resilience in adolescents from Lima and Huanta, according to the family type they belong to. The research’s design is descriptive-comparative in nature. The sample for the study was composed of 510 adolescents of both genders, aged between 12 and 17. The first applied instrument was a data form to collect information about each adolescent’s family type. The second applied instrument was the Resilience Scale (RS) created by Wagnild and Young. The results of the research showed no significant differences statistically between the resilience levels in adolescents from Lima and Huanta based on their family type, with .708 to the Kruskal-Wallis K Test. It was found that adolescents from Huanta have higher levels of self-assurance in comparison to their peers from Lima. Also, it was found that female adolescents from Lima and Huanta are more satisfied with their lives.